ANALISIS FAKTOR TERJADINYA PERUBAHAN EKOSISTEM SAWAH - Ana Alimatul Himmah; Siti Zahrotul Choiriyah; Alfiatur Rohmah; Achmad Ali Fikri (Florea : Jurnal Biologi dan Pembelajarannya, 2021)
This study aims to determine the factors of changes in the rice field ecosystem. The method used in this research is descriptive qualitative. Data collection techniques by observation, interviews and supported by literature study from relevant reference sources. Based on the results of observations, interviews and literature studies that have been conducted, three factors have been found to change the rice field ecosystem. Starting from the most influential factors, namely the use of fertilizers and chemicals, genetic engineering, and land narrowing. With this, the authors hope to provide information to the community about changes in the ecosystem caused by their own exploitation of agricultural land.